Determinants of Exchange Rate Volatility: New Estimates from Nigeria - Hassan, Adamu; Abubakar, Mika’ilu; Dantama, Yusuf Umar (Eastern Journal of Economics and Finance, 2017)
This study investigates the sources of exchange rate volatility in Nigeria from 1989Q1 to 2015Q4. The volatility of exchange rate was obtained through the use of Autoregressive Conditional Heteroscadasticity (ARCH) model. The study further employed Autoregressive Distributed Lag (ARDL) model and Granger Causality test to estimate the relationship between exchange rate volatility and its determinants in Nigeria. The findings revealed that net foreign asset and interest rate have positive and statistically significant impact on exchange rate volatility while fiscal balance, economic openness and oil price have positive and statistically insignificant impact on exchange rate volatility. Furthermore, nominal gross domestic product has negative and statistically insignificant impact on exchange rate volatility. Result of Granger Causality test reveals that there is bidirectional causality running from both fiscal balance and exchange rate volatility whereas unidirectional causality runs from economic openness and oil price to exchange rate volatility. There is however, no evidence of causality between net foreign asset, nominal gross domestic product and interest rate on one hand and exchange rate volatility. Consistent with the findings, the study recommends that government should increase the holding of foreign asset in order to ensure surplus or balance in the current account and there is need for the Central Bank of Nigeria to ensure a stable interest rate in the economy with a view to realize stable exchange rate.